1997
DOI: 10.1182/blood.v90.7.2680
|View full text |Cite
|
Sign up to set email alerts
|

Wiskott-Aldrich Syndrome/X-Linked Thrombocytopenia: WASP Gene Mutations, Protein Expression, and Phenotype

Abstract: Wiskott-Aldrich syndrome (WAS) and X-linked thrombocytopenia (XLT), caused by mutations of the WAS protein (WASP) gene, represent different phenotypes of the same disease. To demonstrate a phenotype/genotype correlation, we determined WASP gene mutations in 48 unrelated WAS families. Mutations included missense (20 families) and nonsense (eight) mutations located mostly in exons 1 to 4, and splice-site mutations (seven) and deletions and insertions (13) located preferentially in exons 7 to 11. Both genomic DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
59
1
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(67 citation statements)
references
References 41 publications
4
59
1
3
Order By: Relevance
“…Such disorders are conventionally diagnosed using genetic analysis, but it may take several weeks or months to identify a particular gene mutation. In the case of WAS, several groups have established that WASp expression is absent or abnormal in the majority of patients found to have gene mutations (Remold-O'Donnell et al, 1997;Zhu et al, 1997). Indeed, we have previously reported the use of two anti-WASp sera to confirm the absence of WASp in PBMCs of patients suffering from the disease (MacCarthy-Morrogh et al, 1998).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Such disorders are conventionally diagnosed using genetic analysis, but it may take several weeks or months to identify a particular gene mutation. In the case of WAS, several groups have established that WASp expression is absent or abnormal in the majority of patients found to have gene mutations (Remold-O'Donnell et al, 1997;Zhu et al, 1997). Indeed, we have previously reported the use of two anti-WASp sera to confirm the absence of WASp in PBMCs of patients suffering from the disease (MacCarthy-Morrogh et al, 1998).…”
Section: Discussionmentioning
confidence: 88%
“…From a clinical perspective, one might speculate that, if the abnormal protein in P12 retained partial function, the grandson P11 who has absent protein may suffer a more severe clinical course. Indeed, other studies have suggested that less severe phenotypes may retain residual WASp expression (Zhu et al, 1997;Shcherbina et al, 1999), although in both reports expression was studied in Epstein-Barr virus (EBV)-immortalized B-cell lines that may affect protein stability. The detection of abnormal-sized bands following immunoblot analysis for WASp has not been previously reported or used in the establishment of a diagnosis in WAS and XLT.…”
Section: Discussionmentioning
confidence: 99%
“…In classic WAS patients, WASP expression is not detected. Most XLT patients have missense mutations in the WASP amino terminus (within residues 1-137), and express the mutant proteins at a lower concentration than normal subjects (Zhu et al, 1997;Imai et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Wiskott-Aldrich syndrome (WAS) is a rare X-linked disorder with variable clinical phenotypes that correlate with the type of mutations in the WAS protein (WASP) gene (1). The WASP gene is composed of 12 exons containing 1823 base pairs and encodes a 502-amino acid protein that appears to be of central importance for the function of hematopoietic stem cells (2). Mutations of WASP gene are located throughout the gene, although some hot spots have been identified (3).…”
mentioning
confidence: 99%
“…Mutations, on the other hand, result in residual expression of a full-length point-mutated WASP, are often associated with X-linked thrombocytopenia (XLT) (5), corresponding to a longer life expectancy (6). A scoring system based on clinical symptoms has been developed to differentiate these distinct clinical phenotypes caused by WASP gene mutations (2,3,7). Autoimmune complications are frequently observed in WAS and patients who develop autoimmune diseases are assigned to a high-risk group with poor prognosis (1).…”
mentioning
confidence: 99%